(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The problem of the importance of the financial security of business development in the agricultural sector of economy is covered in this article. The importance of inner and outer sources of financing during the organization of their practice has been determined. Special attention is payed towards the problematic questions of build-up of the capacities of financial resources, determination of the optimization of sources of their formation. The problematic questions of bank lending and the implication of the financial resources through the stock market are also covered below. Great attention is directed towards the importance of the state financial assistance for agricultural sector of economy development.